Malachi - Schart, Aaron (W. Kohlhammer GmbH, 2021)
This commentary proceeds by first offering a synchronic view of the canonical final text of Malachi, especially the argumentation in the disputation speeches. Then the history of the text's origins is reconstructed, revealing an originally independent collection of disputation speeches. The additions provide some precision, introduce motifs from other writings, or accommodate the text to changing historical frameworks. In a third move the reader's view is directed beyond the Malachi document itself: as the last writing in the Book of the Twelve Prophets, Malachi refers back to other prophetic writings. The New Testament in turn adopts sayings from Malachi and develops them further. Finally, Schart investigates the theological relevance of the book. This commentary proceeds by first offering a synchronic view of the canonical final text of Malachi, especially the argumentation in the disputation speeches. Then the history of the text's origins is reconstructed, revealing an originally independent collection of disputation speeches. The additions provide some precision, introduce motifs from other writings, or accommodate the text to changing historical frameworks. In a third move the reader's view is directed beyond the Malachi document itself: as the last writing in the Book of the Twelve Prophets, Malachi refers back to other prophetic writings. The New Testament in turn adopts sayings from Malachi and develops them further. Finally, Schart investigates the theological relevance of the book
Keywords: Dodekapropheton; Kommentar; Prophetie